2013
DOI: 10.1103/physreve.88.062405
|View full text |Cite
|
Sign up to set email alerts
|

Effects of interface sliding on the formation of telephone cord buckles

Abstract: Sliding at interface during thin film buckling was reported by recent atomistic simulations. A stability analysis under the Föppl-von Kármán plate theory is performed to investigate the effect of interface sliding on the transition of a straight-sided blister to the telephone cord buckle in biaxially compressed thin films on rigid substrates. It is shown that the critical stress and the wavelength of the telephone cord buckle significantly increase as the interface sliding is noticeable in comparison with the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
11
0

Year Published

2014
2014
2025
2025

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 20 publications
(11 citation statements)
references
References 31 publications
0
11
0
Order By: Relevance
“…8), we believe that the waviness period of the TC blister may be inherited from the instability wavelength. The deviation from λ / b ≈2 is attributed that λ / b also depends on the adhesion with a non-trivial relationship1416. Usually the increase of A / λ releases more the elastic energy in the biaxially compressed film deposited on the substrate, while it has to increase the mixed-mode-dependent adhesion energy.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…8), we believe that the waviness period of the TC blister may be inherited from the instability wavelength. The deviation from λ / b ≈2 is attributed that λ / b also depends on the adhesion with a non-trivial relationship1416. Usually the increase of A / λ releases more the elastic energy in the biaxially compressed film deposited on the substrate, while it has to increase the mixed-mode-dependent adhesion energy.…”
Section: Resultsmentioning
confidence: 99%
“…In addition, the ratio may be not constant and change with the interfacial adhesion and the film-to-substrate modulus ratio111213141516. The zigzag undulation feature of the TC buckle has been replicated by numerical investigations51516171819.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…17 It has also been demonstrated that the height and width of the buckles are related to the properties of the cohesive zone in both FEM simulations 18,19 and atomistic simulations. 16,20 Scanning electron microscopy (SEM) images of a Ti 0.39 Si 0.04 N 0.57 thin film grown on a silicon substrate using DC reactive magnetron sputtering 4 showed that various buckling patterns were generated including circular blisters, straight-sided wrinkles and telephone cords with widths or diameters in the range of 15-25 µm. Moreover, most of the buckling patterns exhibited cracks at their apexes and/or at the bottom of the buckle (Fig.…”
mentioning
confidence: 99%
“…10,[12][13][14][15] This approach is valid when the interface strength is infinite at the delamination front. 14,16 It has been shown that by taking into account interface adhesion using a cohesive zone model, the kinematics of a propagating telephone cord buckle can be simulated. 17 It has also been demonstrated that the height and width of the buckles are related to the properties of the cohesive zone in both FEM simulations 18,19 and atomistic simulations.…”
mentioning
confidence: 99%